Muslim Ban during Trump’s Presidency through the Target Population Framework - Cahyo Edi, Ashari; Lin, Poyung; Neupane, Kaubin; Topal, Reyhan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
One of the controversies that defined Donald Trump’s presidency was his travel ban policy, which targeted immigrants from many Muslim-majority countries in 2017. While researchers have analyzed the rhetoric, discourse, and indirect speech acts of President Trump and American politicians to fully understand the enforcement of the travel ban, the number of studies investigating how politicians utilize the social construction of immigrants to support or oppose the travel ban is limited. Hence, it is crucial to thoroughly study how political actors socially construct immigrants to justify their policy positions on the travel ban. In this article, we contextualize the travel ban policy within the literature on the social construction of target populations, one of the prominent theories of policy processes. To that end, we examine four types of data sources: legal documents, relevant tweets posted by politicians, think tank publications (op-eds, releases, and commentaries), and news articles published during the travel ban debates. In light of our analysis, we find that not only policymakers but also members of the judicial system, news media sources, and think tanks construct immigrant identities in a way that justifies their policy positions on the travel ban. Our findings underscore the need for a nuanced and well-rounded debate on travel restrictions concerning the reconstruction and reimagination of immigrant identities by various actors. We also contend that future research could greatly benefit from analyzing the social construction of immigrants by different policy actors in a comparative fashion.